Tempos de pandemia, tempos de desafios: um estudo sobre o trabalho com a língua portuguesa no ensino fundamental 1 em foz do iguaçu - pr - Dourado, Malta Moreira (2023)
With the decision of the Ministry of Education to close schools to contain the spread of Covid-19, infectious disease caused by the SARS-CoV-2 virus were introduced, on emergency basis, the modalities of remote teaching and hybrid teaching for the continuation of fundamental teaching I in the municipal network of Foz do Iguaçu – PR during the pandemic. As a result, the teaching modalities that were presented at that juncture left the dialogue limited; interaction with the student, so essential in this schooling phase, was restricted to clarifying students' doubts in relation to discursive practices in the Portuguese language through electronic devices. In view of the above, some questions arose, among which we chose for this study: How did teachers experience – and experience – the process of face-to-face/remote, remote/hybrid and hybrid/face-to-face teaching in relation to the teaching of Portuguese language discursive practices in a pandemic context? With the purpose of finding answers to this problem, we set out, as a general objective, to investigate the perceptions and challenges experienced by teachers in teaching Portuguese language discursive practices in one of the municipal schools in Foz do Iguaçu. In order to achieve the proposed objective, we decided on social research with a qualitative, interpretive approach, of the case study type, affiliated with Applied Linguistics. The theoretical foundation is guided by concepts from the Bakhtin Circle, plus the Dialogical Studies of Language, which promote the interpretation and discussion of the generated data. Therefore, considering the fact that we do not know whether, in the near future, we will have new unpredictable situations like this one, which would require emergency strategies in education, it is strictly pertinent that there be discussions, analyzes and reflections on the part of the educational sphere regarding the teaching of the Portuguese language and, above all, the impacts caused by the pandemic and its labor, socio-affective and pedagogical implications, so that, subsequently, municipal, state and federal managers can open space for discussion and implementation of new public policies, the service of an emancipatory education, which implies the quality of post-pandemic education.